2017
DOI: 10.1038/ncomms14633
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of inducible CRISPR guide RNAs for de novo assembly of transcriptional programs

Abstract: CRISPR-based transcription regulators (CRISPR-TRs) have transformed the current synthetic biology landscape by allowing specific activation or repression of any target gene. Here we report a modular and versatile framework enabling rapid implementation of inducible CRISPR-TRs in mammalian cells. This strategy relies on the design of a spacer-blocking hairpin (SBH) structure at the 5′ end of the single guide RNA (sgRNA), which abrogates the function of CRISPR-transcriptional activators. By replacing the SBH loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 41 publications
2
93
0
Order By: Relevance
“…1d, 2). Importantly however, when tested in a gRNA functional reporter assay 4,22 , all tRNAs with the exception of rice tRNA Gly enabled efficient transcriptional activation at levels equivalent to U6, in the absence of any additional Pol-II or Pol-III promoters ( Supplementary Fig. 1e, f, 3a).…”
Section: Rationale For Trna Variant Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…1d, 2). Importantly however, when tested in a gRNA functional reporter assay 4,22 , all tRNAs with the exception of rice tRNA Gly enabled efficient transcriptional activation at levels equivalent to U6, in the absence of any additional Pol-II or Pol-III promoters ( Supplementary Fig. 1e, f, 3a).…”
Section: Rationale For Trna Variant Screeningmentioning
confidence: 99%
“…To allow the functional analyses to be performed only on cells which had received all necessary plasmids, we inserted a SV40 promoter-mCherry-SV40 polyA cassette into the backbone of the 8xCTS2-mCMVp-ECFP construct (REF 22 ) between the PciI and SalI sites. The insert was amplified from an available plasmid using primers which added the PciI and SalI sites respectively (Forward: TGCTTACATGTGGAATGTGTGTCAGTTAG, Reverse:…”
Section: Cloning and Construct Assembly -8xcts2 Reporter Modificationmentioning
confidence: 99%
“…Systematic mapping of the structure and sequence properties of functional gRNAs has revealed that Cas9 activity is tolerant to significant modifications the standard gRNA structure, 21,22 facilitiating introduction of auxiliary domains that enable conditional control of gRNA activity via structural changes induced by small-molecules, 23,24 protein-bound RNAs, 25 nucleases, 26 or nuclease-recruiting DNAs. 26 Alternatively, the activity of standard gRNAs has been modulated by antisense RNAs 27 or by photolysis of antisense DNAs incorporating photocleavable groups. 28 Here, pursuing the scRNA paradigm of programmable conditional regulation based on dynamic RNA nanotechnology, and leveraging information on tolerated modifications of standard gRNA structure, we set out to engineer conditional guide RNAs (cgRNAs) that change conformation in response to an RNA trigger X to conditionally direct the function of dCas9 to a target gene Y.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in some of our tests below, we used binding of a fluorescently tagged MS2 viral coat protein to an MS2 RNA hairpin segment within the design as an output ( Figure 1A & 1B); such interactions underlie most systems for CRISPR interference and activation and in situ RNA visualization. [2][3][4][5][6][19][20][21] The user only needs to specify the sequence and 'active' secondary structure of this output element and RiboLogic will place this sequence relative to the input aptamer element and optimize surrounding sequences during its design process.…”
mentioning
confidence: 99%